Infection, inflammation,and lung function decline in infants with cystic fibrosis - Pillarisetti, N.; Williamson, E.; Linnane, B.; Skoric, B.; Robertson, C.; Robinson, P.; Massie, J.; Hall, Graham; Sly, P.; Stick, S.; Ranganathan, S. (American Thoracic Society, 2011)
Rationale: Better understanding of evolution of lung function in infants with cystic fibrosis (CF) and its association with pulmonary inflammation and infection is crucial in informing both early intervention studies aimed at limiting lung damage and the role of lung function as outcomes in such studies. Objectives: To describe longitudinal change in lung function in infants with CF and its association with pulmonary infection and inflammation. Methods: Infants diagnosed after newborn screening or clinical presentation were recruited prospectively. FVC, forced expiratory volume in 0.5 seconds (FEV0.5), and forced expiratory flows at 75% of exhaled vital capacity (FEF75) were measured using the raised-volume technique, and z-scores were calculated from published reference equations. Pulmonary infection and inflammation were measured in bronchoalveolar lavage within 48 hours of lung function testing. Measurements and Main Results: Thirty-seven infants had at least two successful repeat lung function measurements. Mean (SD) z-scores for FVC were −0.8 (1.0), −0.9 (1.1), and −1.7 (1.2) when measured at the first visit, 1-year visit, or 2-year visit, respectively. Mean (SD) z-scores for FEV0.5 were −1.4 (1.2), −2.4 (1.1), and −4.3 (1.6), respectively. In those infants in whom free neutrophil elastase was detected, FVC z-scores were 0.81 lower (P = 0.003), and FEV0.5 z-scores 0.96 lower (P = 0.001), respectively. Significantly greater decline in FEV0.5 z-scores occurred in those infected with Staphylococcus aureus (P = 0.018) or Pseudomonas aeruginosa (P = 0.021). Conclusions: In infants with CF, pulmonary inflammation is associated with lower lung function, whereas pulmonary infection is associated with a greater rate of decline in lung function. Strategies targeting pulmonary inflammation and infection are required to prevent early decline in lung function in infants with CF.